Evaluation of Local History Education in the Merdeka Curriculum: Challenges and Implementation in Regional Schools - Ryanto, Ammar Zhafran; Manurung, Nadya Tridrisna (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to describe the implementation of local history learning assessments within the Merdeka Curriculum and to analyze the challenges faced at senior high schools (SMA/MA) in Tebing Tinggi City, North Sumatra. Tebing Tinggi City possesses a significant wealth of local history, including relics of the Padang Kingdom, Dutch colonial sites, the Bloody Incident of December 13, 1945, and multicultural ethnic diversity. The study employs a descriptive qualitative approach with a multisite case study design across three high schools (SMA/MA) selected through purposive sampling. Data were collected via indepth interviews, classroom observations, focus group discussions, and documentation. Data validity was tested through triangulation of sources and techniques, as well as member checking. Analysis utilized the interactive model by Miles, Huberman, and Saldana. The results indicate: (1) the evaluation instruments used by teachers have not systematically integrated the local history of Tebing Tinggi; (2) there are four main groups of challenges: pedagogical, learning resources, infrastructure, and institutional policy; (3) students respond positively to local history based evaluations; and (4) teachers’ adaptation efforts are independent and not yet systemic. The study underscores the urgency of developing integrated evaluation standards for the local history of Tebing Tinggi within the Merdeka Curriculum.